If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = 10x + -26 Reorder the terms: -6 = -26 + 10x Solving -6 = -26 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -6 + -10x = -26 + 10x + -10x Combine like terms: 10x + -10x = 0 -6 + -10x = -26 + 0 -6 + -10x = -26 Add '6' to each side of the equation. -6 + 6 + -10x = -26 + 6 Combine like terms: -6 + 6 = 0 0 + -10x = -26 + 6 -10x = -26 + 6 Combine like terms: -26 + 6 = -20 -10x = -20 Divide each side by '-10'. x = 2 Simplifying x = 2
| x^2-13x+61=0 | | c+3.8=5.2 | | -5(x-9)=35 | | 4x^2=20x-24 | | 7m-12-2m+8= | | x^2=x+20 | | 3-11n=9+5x | | -0.125(16x-208)=-1x+12x | | t^2+30t-3675=0 | | x+4=8.1 | | 49t^2+30t-75=0 | | 7k+8+7k=22 | | .24(x+55)+.47(x+70)=-42.65 | | 4x-8=40 | | 16x^2-20x=6 | | 1x+0.6y=(-1.5) | | 3(2d+1)=6-4(3d-3) | | 2m+6=10m+14 | | 1xd= | | 2m+6=10+14 | | 8c-24=fraction | | 0.22x+0.17y=9 | | 0.04x-0.01y=0 | | 7r-11=-7+5r | | 9r-20=-32+6r | | 3x^2+36x^2+108x=0 | | 200+x=1.5x | | c^2+4c-45=0 | | 6x+2=(x-22) | | 4(3+4x)-5=71 | | 6z+3=8z-5 | | 3(2x-2)=24 |